The Influence of Entrepreneurial Spirituality and Social Media Adoption on the Sustainability of MSME Performance Mediated by Innovation Capability (Survey on MSMEs in the Tourism Area Sunan Drajat Lamongan) - Shoimah, Siti; Muhajir, Ali; Rosyid, Muhammad (KnE Social Sciences, 2024)
Technological advancements, computerization, and globalization have made businessescompetitiveacrossallindustries. Micro, small, and medium-sizedenterprises (MSMEs) continue to encounter difficulties with resource scarcity and technology adoption, although accounting for over 80% of employment and contributing to 61.97% of the GDP (gross domestic product). The Sunan Drajat Lamongan Religious Tourism Area is a home to hundreds of MSMEs, ranging in size from apparel and souvenir shops to restaurants. The number of visitors rises dramatically throughout the holiday season before becoming quiet, as is common with tourism in general. Entrepreneurship is a key factor in economic growth and serves as the primary driving force for innovative and long-term growth. By leveraging social media to enhance a company’s competitive advantage throughout the entrepreneurship and operation phases, entrepreneurs who possess an entrepreneurial mindset can aid their organizations in efficiently adapting their organizational framework and processes, thereby mitigating environmental conflicts and tensions within the intricate framework of a dynamic business environment. By using social media, MSMEs may reach their target audience with content and information without having to personally meet them. Social media also offers information in the form of customer reviews of goods, services, and even new ideas for sustainable MSMEs. This study aimed to determine how MSMEs’ use of social media and their ability for innovation can impact their success in Sunan Drajat Lamongan’s religious tourism industry. The data were obtained from 132 small and medium-sized enterprises using questionnaires. Path Least Square (PLS) and descriptive analysis were the methods utilized to analyze the data. Keywords: entrepreneurial spirituality, social media adoption, innovation capability, sustainability of MSMEs performance